Are women more ethical than men? / Avelia Othman - Othman, Avelia; Zulkefli, Salizuana (2005)
Ethics has been a vital ingredient in any human being's life especially for Asian people. Many universities have attempted to address the importance of being ethical by making a course and activites on ethics.